2008
DOI: 10.1300/j069v27n02_09
|View full text |Cite
|
Sign up to set email alerts
|

Underlying Pathophysiology of HCV Infection in HIV-Positive Drug Users

Abstract: HCV and HIV infections are very common among injection drug users (IDUs). It is well known that 80-90% of HIV-infected IDUs are also infected with HCV. Furthermore, patients with HCV/HIV co-infection are at a higher risk of progressing to end-stage liver disease, namely cirrhosis. Even though there is increasing global awareness of HCV/HIV co-infection and extended therapeutic programs for this infected population, little is known about the HCV/HIV pathophysiology that mediates the rapid progression to hepatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…Analysis of gene expression profiles in the HCV/HIV mono-infected or co-infected patients would provide a unique opportunity to understand the mechanisms. It is reported that factors, such as direct viral effects, the immunologic alterations especially the specific T-cell response, have played important roles in the disease progression [ 11 - 13 ]. CD4 + T cells, the major HIV target cells, also play an essential role in HCV clearance [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of gene expression profiles in the HCV/HIV mono-infected or co-infected patients would provide a unique opportunity to understand the mechanisms. It is reported that factors, such as direct viral effects, the immunologic alterations especially the specific T-cell response, have played important roles in the disease progression [ 11 - 13 ]. CD4 + T cells, the major HIV target cells, also play an essential role in HCV clearance [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies showed HCV infection stimulates cytokine production. [91] However, with HCV infection and alcohol intake, T h 1 and not T h 2 cytokines were elevated. [297] Up-regulation of intrahepatic T h 1 cytokines, IL-2 and IFNg, and downregulation of T h 2 and in serum, IL-10 increase was detected in prior studies.…”
Section: Drug Abuse and Immunementioning
confidence: 96%
“…Mechanisms of accelerated disease progression in HIV/HCV-coinfection have not been fully determined. However, disturbances in virus-specific T cell responses via altered activity of regulatory T cells (T reg ) are thought to play an important role [6][7][8] in infections caused by HIV, HCV, and herpes virus [9][10][11][12]. Prior work has shown T reg expansion in the course of HIV and/or HCV infection [13][14][15].…”
Section: Introductionmentioning
confidence: 99%